Paediatric Dupuytren′s disease - Pradeoth Mukundan Korambayil; Anto Francis Padikala (Indian Journal of Plastic Surgery)
Dupuytren′s disease of the hand has only been rarely reported in children and is rarer still in infants. Only a few histologically confirmed diagnoses are found in literature. We report a case in a 4-month-old infant with Dupuytren′s disease of palm and thumb who required surgery at 6 months of age. Histology confirmed the diagnosis of Dupuytren′s disease. The purpose of this report is to show the importance of differential diagnosis of nodules and fibrotic bands in children′s hands as paediatric patients may be seen by a variety of treating physicians, not only plastic surgeons or pathologists.